Exploring Sport As Effective Engagement Mechanism For Youth Empowerment And Youth Development In Nigeria’s Niger Delta Region - Nwaokugha, Douglas O. (Archives of Business Research, 2021)
The Niger Delta region of Nigeria is synonymous with crisis occasioned by militancy, agitations and insurgency from the youth, who in recent times have become aware of the neglect, marginalization, human rights abuses, environmental degradation etc, people of the region suffer in the hands of the Nigerian government and Multinational Corporations that explore and exploit the Niger Delta environment for its rich natural resources. Investing time in militancy, agitations and insurgency as presently spearheaded by youth in the region has created more problems than solve the Niger Delta crises. Using the philosophical method, this paper makes a case on how sport can be an effective engagement mechanism for youth engagement and youth empowerment. The paper sees sport as a human engagement whose effective exploration and utilization can lead to the empowerment of youth in Nigeria’s Niger Delta and consequently recommends that states intervention agencies, politicians and philanthropists should make the provision of sport infrastructure a topmost priority for youth development and empowerment. The paper strongly maintains that policies that target youth empowerment in the Niger Delta region of Nigeria will surely be a foundation for sustainable peace and stability not only in Nigeria but across the globe.